Land‐atmosphere exchange of methane from soil thawing to soil freezing in a high‐ A rctic wet tundra ecosystem - Torbern Tagesson; Meelis Mölder; Mikhail Mastepanov; Charlotte Sigsgaard; Mikkel P. Tamstorf; Magnus Lund; Julie M. Falk; Anders Lindroth; Torben R. Christensen; Lena Ström (Global Change Biology, 2012)
The land‐atmosphere exchange of methane ( CH 4 ) and carbon dioxide ( CO 2 ) in a high‐ A rctic wet tundra ecosystem ( R ylekærene) in Z ackenberg, north‐eastern G reenland, was studied over the full growing season and until early winter in 2008 and from before snow melt until early winter in 2009. The eddy covariance technique was used to estimate CO 2 fluxes and a combination of the gradient and eddy covariance methods was used to estimate CH 4 fluxes. Small CH 4 bursts were observed during spring thawing 2009, but these existed during short periods and would not have any significant effect on the annual budget. Growing season CH 4 fluxes were well correlated with soil temperature, gross primary production, and active layer thickness. The CH 4 fluxes remained low during the entire autumn, and until early winter. No increase in CH 4 fluxes were seen as the soil started to freeze. However, in autumn 2008 there were two CH 4 burst events that were highly correlated with atmospheric turbulence. They were likely associated with the release of stored CH 4 from soil and vegetation cavities. Over the measurement period, 7.6 and 6.5 g C m −2 was emitted as CH 4 in 2008 and in 2009, respectively. R ylekærene acted as a C source during the warmer and wetter measurement period 2008, whereas it was a C sink for the colder and drier period of 2009. Wet tundra ecosystems, such as R ylekærene may thus play a more significant role for the climate in the future, as temperature and precipitation are predicted to increase in the high‐ A rctic.